-8x-18=-12x+34

Simple and best practice solution for -8x-18=-12x+34 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x-18=-12x+34 equation:


Simplifying
-8x + -18 = -12x + 34

Reorder the terms:
-18 + -8x = -12x + 34

Reorder the terms:
-18 + -8x = 34 + -12x

Solving
-18 + -8x = 34 + -12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12x' to each side of the equation.
-18 + -8x + 12x = 34 + -12x + 12x

Combine like terms: -8x + 12x = 4x
-18 + 4x = 34 + -12x + 12x

Combine like terms: -12x + 12x = 0
-18 + 4x = 34 + 0
-18 + 4x = 34

Add '18' to each side of the equation.
-18 + 18 + 4x = 34 + 18

Combine like terms: -18 + 18 = 0
0 + 4x = 34 + 18
4x = 34 + 18

Combine like terms: 34 + 18 = 52
4x = 52

Divide each side by '4'.
x = 13

Simplifying
x = 13

See similar equations:

| 3x/2+7x-7=3(2x+1) | | 2a+2a=2a | | 17-(3m+7)=2+3m-16 | | 3(4z+8)-36= | | -8-18=-12+34 | | -20D-3+3D=11D+5-8 | | 80.5=7(m+3.6) | | 5+44x=53+8x | | 7=9x-7 | | 7z-7=5+32 | | b=4b | | 34.95(5)+x(.49)=200 | | 6+7x=-8 | | 3(x-6)=2 | | -11-5(t-3)= | | y=(x^2+1)(12x)-(6x^2+7)(2x) | | 44-5x=53-8x | | 7(x-2)+2=-12 | | .10x+.35(50)=23.5 | | 4y+6=8y+2 | | 13x-203=6x-7 | | 5+2t-2=6t+9-2t | | 10.4+3.2f=5f+4 | | 4x-6=4(x+1) | | 3(-9)+2= | | -6x-17=-125 | | -23+22=m-4 | | v-7.92=1.9 | | 31-(3x+5)=3(x+4)+x | | 10x-17=12x+21 | | -0.6x-0.3x+8=-1 | | 12x-5=7x+50 |

Equations solver categories